IMPLEMENTASI KEBIJAKAN PERATURAN BUPATI NOMOR 66 TAHUN 2021 PENEMPATAN PEDAGANG PASAR TERAPUNG KABUPATEN INDRAGIRI HILIR - Rita Susanti; Sujianto Sujianto (Cross-border, 2023)
Tembilahan Floating Market is the largest traditional market in Indragiri Hilir Regency which is a form of the existence of a floating market in Tembilahan City. So far, the Disperindag or the Industry and Trade Service in Tembilahan have faced several problems, namely market traders still putting their wares in the parking lot and funds budgeted for market facilities for traders are still minimal. This study aims to see how the relocation of floating market traders in Indragiri Hilir Regency as a market that has floating buildings can be well organized. This research was used using qualitative research methods by analyzing descriptively according to the concept of Implementation Theory. In data collection techniques, researchers used interview, observation, and documentation techniques. This researcher also uses informants or sources who know and can provide clear information. The results of this study indicate that market management is not running properly. This is evidenced by the fact that Communication, Resources, Disposition and Organizational Structure are still not optimal. The inhibiting factors in the relocation of market traders are Budget, Merchant Awareness, Switching Fees. This is due to the lack of support and lack of assistance from the Government of Indragiri Hilir Regency, so that the relocation of floating market traders has not been optimal.